"Why do I obsess about my child's flaws?": Assessing the role of parental self‐vulnerabilities in parent–child relationship obsessive compulsive disorder (ROCD) symptoms. (7th April 2020) - Levy, Assaf; Tibi, Lee; Szepsenwol, Ohad; Doron, Guy
Abstract: Objective: Relationship obsessive compulsive disorder (ROCD) is a manifestation of obsessive compulsive disorder (OCD) that refers to obsessions, doubts, and compulsive behaviours focusing on one's relationship and relationship partner. ROCD symptoms occur in various types of relationships including parent–child dyads, involving obsessional preoccupations with the perceived flaws of one's child (parent–child ROCD symptoms). Such preoccupations have been shown to be associated with decreased mood and significant parental distress. We examined the double self‐vulnerability hypothesis—that the co‐occurrence of parental contingency of self in specific domains (i.e., intelligence and appearance) and child‐value contingent self‐worth would be associated with increased parent–child ROCD symptoms. Method: A total of 175 parents participated in the study and completed self‐report questionnaires to assess ROCD and depressive symptoms and parental self‐contingencies. We used linear regression with simple slope analyses to estimate interaction effects. Results: Parents whose self‐worth were strongly dependent on their child's perceived value showed higher parent–child ROCD symptoms, particularly when co‐occurring with parental intelligence and appearance self‐contingencies. These findings were maintained when controlling for depression symptoms, parental age, and gender. Conclusions: Results supported the double self‐vulnerability hypothesis suggesting that parents with child‐value and domain‐relevant self‐vulnerabilities might be susceptible to child‐related obsessions. More research is needed to further explore susceptibility of vulnerable parents to the development and maintenance of parent–child ROCD symptoms.